دراسة شعاعية لتقييم العلاقة بين الكثافة المعدنية العظمية الموضعية والثخانات العظمية حول الزرعات السنية (دراسة مقارنة مع الليزر اللين) - مشلح, عمار; حرفوش, منير; عزالدين, رامي (Latakia University Journal -Medical Sciences Series, 2013)
تطورت تطبيقات الليزر اللين (bio-stimulating laser) في تحسين الكثافة المعدنية العظمية الموضعية والتي تعدّ العامل الأهم في نجاح الزرعات السنية. تهدف هذه الدراسة إلى تقييم قدرة مشعر نسبة العظم الاسفنجي إلى العظم القشري (TCR) Trabecular to Cortical bone Ratio - كمشعر بسيط سهل القياس- في التعبير عن كثافة العظم الموضعية لنستطيع منه التنبؤ بنجاح الزرعات السنية. شملت الدراسة 40 مريضاً أجري لهم زرعات مفردة في منطقة الأرحاء السفلية، ومقسمين إلى مجموعتين: 20 مريضاً أجري لهم الزرع مع تطبيق الليزر اللين وهو ليزر الغاليوم – ألمنيوم _ أرسنيد (GaAlAs) (طول الموجة 830nm) و20 مريضاً أجري لهم الزرع دون تطبيق الليزر اللين. استُخدمت الصور الذروية العادية Analog مع مدرج معايرة من الألمنيوم النقي، واستخدم برنامج الديجورا الطبي لقياس الكثافة العظمية الشعاعية في الصورة الذروية، وتم إجراء تصوير بانورامي مقطعي لدراسة الـ TCRوتم حساب المشعرين الشعاعيين ("نسبة الثخانة X نسبة الكثافة"، "ثخانة الألمنيوم المكافئة")؛ خلال الفترات: قبل الزرع وبعد 3 و 6 و 9 أشهر من الزرع. وجدت الدراسة علاقة ارتباط خطية قوية بين الـ TCr، وكل من "نسبة الكثافة X نسبة الثخانة"( 0.001> P، R2 = 0.842 ، 36(r = 0.8. و"ثخانة الألمنيوم المكافئة" ( 0.001> P، R2 = 0.6567 ، 35(r = 0.8. وبالتالي فإن مشعر الـ TCr يعبر عن كلا المشعرين الذين يعبران عن الكثافة العظمية الموضعية، مما يعني أن الـ TCr مرتبط بهذه الكثافة، وبالتالي نستفيد منه كطريقة سهلة للتنبؤ بنوعية العظم وتوقع نجاح الزرعات السنية. Soft laser applications continue to improve local bone mineral density which is considered the most important factor in dental implant success. This study aims to evaluate the Trabecular to Cortical bone ratio (TCr) index -as a simple easy measurement index- that expresses the bone mineral density. This is to be able to predict the success of dental implants. The study included 40 patients, who had a single implant in the lower molar region. The patients are divided into two groups: 20 patients had an implant with a soft laser application, i.e. GaAlAs laser (wavelength 830 nm), and 20 patients had an implant without a soft laser application. Ordinary Analog periapical radiographs were used with calibration Stepwedge of pure aluminum, a medical Dijora program was used to measure radiographically local bone density in the periapical radiographs, and a panoramic Tomography was made to study TCr and two bone density indices (thickness ratio x density ratio) and (equivalent Aluminium thickness). All were measured during the period before implantation and 3, 6, and 9 months after the implantation. The study found a strong linear correlation between the TCr and (thickness ratio x density ratio) 0.001>P, R2= 0.842 36(r = 0.8. and equivalent Aluminium thickness( 0.001> P, R2 = 0.656735, (r = 0.8). The study shows that TCr index expresses both radiographic indices which reflect the local bone density, which means that the TCr is associated with such density. Therefore, it can be used as an easy way to predict the quality of bone, and prognosticate the success of dental implants.